Alimentação de Potamorhina latior (Spix, 1829) (Characiformes: Curimatidae) e Anodus elongatus (Agassiz, 1829) (Characiformes: Hemiodontidae) em lagos marginais do Rio Acre-Amapá (AC) e Pirapora (AM) - Aranguren, Ligia Célia Neri (2002)
This study analyzesthe feeding habits and behavior of Potamorhina latior (Spix, 1829) (Characiformes: Curimatidae) and Anodus elongatus (Agassiz, 1829) (Characiformes: Hemiodontidae) in two oxbow, of the river Acre, the Amapá lake in the state of Acre and Pirapora lake in the state of Amazonas. During the period from March os 2000 to April of 2001, fish samples in the two lakes were taken and their stomach contents analyzed in order to determine their feeding habit, the preferred items in their diets, the quantitative dynamics of feeding and the similarity between the two species diets, and also to verify the relation of their diets with the seasonal variations of abiotic factors and pluviometric variations. The results showed strong differences in the diets of the species. According to the analyses of feeding frequencies, volume and indices, Potamorhina latior preferred debris followed by algae and invertebrates in the two environments both during the dry and flooding seasons. Debris represented 90% of the stomach contents, and the species can be classified as detritivorous. The same analyses carried out with Anodus elongatus revealed that the items that presented the highest frequencies in occurrence and volume were algae and zooplankton in the two lakes during both seasons, which leads to classifying the species as planktivorous. According to the distribution of algae, Euglenophyceae and Cyanophyceae predominate in the Amapa lake, while Euglenophyceae and Cholophyceae predominated in the Pirapora lake. In the case of zooplankton , Rotifera was the most representative. Spatial and seasonal variations in the diets of both species revealed little relevance, and the oscillation in the proportion of feeding items were related with their availability in the environment. Intensive feeding activity was observed in the flooding period